The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1968
DOI: 10.1080/00071666808415705
|View full text |Cite
|
Sign up to set email alerts
|

The origin of bacteria recovered from the peritoneum and yolk sac of healthy chickens

Abstract: Subclinical peritoneal and yolk sac infections were demonstrated in about 38 and 23 per cent, respectively, of 121 conventional chicks examined during the first 5 days of life; the incidence varied markedly from hatch to hatch. Organisms were demonstrated in the peritoneum and yolk sac of a proportion of gnotobiotic chicks following per os administration of pure cultures of bacteria isolated either from the peritoneum or yolk sac, or from the intestinal tract of conventional chickens. It is concluded that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The transport of bacteria from the lumen to the liver and other tissues is known to occur in the chicken (Fuller & Jayne-Williams, 1968). The transport of bacteria from the lumen to the liver and other tissues is known to occur in the chicken (Fuller & Jayne-Williams, 1968).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport of bacteria from the lumen to the liver and other tissues is known to occur in the chicken (Fuller & Jayne-Williams, 1968). The transport of bacteria from the lumen to the liver and other tissues is known to occur in the chicken (Fuller & Jayne-Williams, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…The flora attached to the caecum wall differs markedly from that of the mouse in that the fusiform bacteria, which form the main epithelial flora of the large intestine of the mouse, are absent. The transport of bacteria from the lumen to the liver and other tissues is known to occur in the chicken (Fuller & Jayne-Williams, 1968. At f i s t sight the adhesion of bacteria to the epithelium might appear to be a preliminary stage of this translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Einheber, 1966). The possibility that migration of bacteria from the gut is necessary for the systemic response is worth considering since it has already been shown that this is a common occurrence in young chicks (Fuller & Jayne-Williams, 1968) and it has been suggested that it might continue undetected throughout life (Fuller & Jayne-Williams, 1970~). Recently the bursa of Fabricius has been shown to harbour a large population of bacteria (Fuller, 1973 6) which differs at least quantitatively from that found in the gut.…”
Section: ( 5 ) Body Temperaturementioning
confidence: 99%
“…Transovarial transmission has been proposed for S. enteritidis (22,23), although there continues to be controversy over the resident site of the pathogen being in the yolk, in the follicular membrane surrounding the yolk, or associated with the albumen (6,12,23,24). Translocation of organisms from the peritoneum to the yolk sac or to the oviduct via macrophages is a possibility suggested by previous studies (5,9,22,24,28,29). Egg contamination by penetration of the shell by organisms present in chicken feces deposited on the outside of the egg as it passes through the cloaca is also feasible (24).…”
mentioning
confidence: 98%